Pengaruh Akuntansi Pertangggungjawaban terhadap Penilaian Kinerja pada KSP Kopdit Plelu Meluk Wolokoli - Kristina Nafatri Ratna Desi (Universitas 45 Surabaya, 2024)
The aim of this research is to find out and analyze the description of the implementation of responsibility accounting, performance assessment and the influence of responsibility accounting on performance assessment at KSP Kopdit Plelu Meluk Wolokoli. This type of research is quantitative descriptive. The population of this study was 30 employees who worked at KSP Kopdit Plelu Meluk and the sampling technique used a saturated sampling technique. The number of respondents in this study was 30 employees. Instrument reliability tests include validity and reliability tests, classical assumption tests include normality tests, heteroscedasticity tests. The data analysis technique uses simple linear regression analysis with hypothesis testing (t test). The results of this research show that Responsibility Accounting (X) has no effect on the Performance Assessment variable (Y).